Uang, Kekerabatan, dan Kehormatan: Studi Etnografi Ritual Pernikahan Saro Doi di Maluku Utara, Indonesia: Money, Kinship, and Honor: An Ethnographic Study of the Saro Doi Marriage Ritual in North Maluku, Indonesia - Fachmi Alhadar; Rudi S. Tawari; Nurfani (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study examines Saro Doi, a marriage tradition practiced in North Maluku, Indonesia. The tradition involves giving money to the bride and groom during a wedding ceremony. The money is usually attached to a small stick resembling a flag and placed in a designated container or handed directly to the couple. While many traditional practices in Indonesia are declining due to social change and modernization, Saro Doi remains widely practiced and continues to evolve within the community. This research employs Malinowski’s functionalism theory to analyze the meanings and functions of the tradition. Using a descriptive qualitative method with an ethnographic approach, data were collected through observations of Saro Doi practices and interviews with selected community informants. The findings indicate that Saro Doi contains complex symbolic meanings related to social status, reciprocity, kinship, and family honor. Functionally, the tradition demonstrates both manifest and latent functions. Its manifest function is facilitating monetary contributions during marriage ceremonies. In contrast, its latent functions include strengthening ethnic and gender identities, fostering social cohesion, promoting transparency, supporting marital ideals, and encouraging community interaction. This study contributes to cultural anthropology and the study of tradition by highlighting the enduring significance of local cultural practices.